The role of heroic doubling in ideologically motivated state and terrorist violence. (4th July 2017) - Griffin, Roger
Abstract: The psychiatrist Robert Lifton developed his model of 'doubling' to account for the capacity of some human beings to commit atrocities in one compartment of their lives, while continuing to maintain normal social relations in their domestic sphere, a phenomenon which he encountered both in interviews with former Nazi doctors working in concentration camps, and with terrorists belonging to the Japanese Aum Shinrikyo cult. By supplementing this model with a theory of heroization based on existential anthropology and Jung's concept of the Shadow, a composite heuristic explanatory paradigm is formed, 'heroic doubling', which may contribute to the empathetic understanding of acts of extreme violence being carried out by individuals who do not present symptoms of psychiatric disorder and maintain normal existences, yet are prepared to kill and be killed for a cause that confers on their lives a sense of transcendent purpose and sacrality.